2015
DOI: 10.1039/c5ra13394g
|View full text |Cite
|
Sign up to set email alerts
|

In silico studies on the origin of selective uptake of carbon dioxide with cucurbit[7]uril amorphous material

Abstract: The efficient capture and storage of flue gases is of current interest due to environment problem. We report the adsorption of flue gases (CO2, N2 and CH4) on amorphous solid Cucurbit[7]uril (CB[7]) computationally. The DFT calculations revealed that CO2 can be adsorbed more strongly inside the cavity of CB[7] compared to N2 and CH4 molecules. The glycoluril units of CB[7] are the preferential sites for the adsorption of CO2 gas molecules. The cooperative binding of CO2 molecules inside the cavity of CB [7] h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Therefore, it is necessary to recover the adsorbed molecules from the receptor molecule. We have performed the calculations to examine the desorption (inverse of the adsorption process) of the gas molecules ,. The B3LYP–D3/6‐31G(d) calculated desorption energies per gas molecules (i. e., CH 4 and N 2 ) given in Table and .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is necessary to recover the adsorbed molecules from the receptor molecule. We have performed the calculations to examine the desorption (inverse of the adsorption process) of the gas molecules ,. The B3LYP–D3/6‐31G(d) calculated desorption energies per gas molecules (i. e., CH 4 and N 2 ) given in Table and .…”
Section: Resultsmentioning
confidence: 99%
“…This geometry has taken from the adsorbed CO 2 molecule with the system 1, A1 (Figure ). The EDA analysis was carried out with M06‐2X/6‐31G(d) level of theory ,. The B3LYP results, in this case, showed erroneous values for such analysis and hence the M06‐2X DFT functional has used.…”
Section: Resultsmentioning
confidence: 99%
“…The energy decomposition analysis (EDA) is carried out at the BP86-D3/SDD//B3LYP-D3/TZ2P level using Amsterdam density functional program package. In EDA, the total binding energy (ΔE bind ) is decomposed into four terms, viz., Pauli repulsion (ΔE Pauli ), electrostatic (ΔE elstat ), orbital (ΔE orb ), and dispersion (ΔE disp ) terms [29]. For performing EDA analysis, the DAO guest molecule is considered as one fragment and the metal-Pillarplexes as the other fragment.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In this regard, CB­[ n ]­s are employed too as a possible macromolecular host for encapsulating different gas molecules. Particularly, CB[6] (structure 1 ) was reported to encapsulate CO 2 , , CO, , noble gas atoms, , CH 4 , C 2 H 2 , and larger hydrocarbons . In fact, Kim et al showed that CB[6] adsorbs CO 2 selectively over CO and CH 4 in the solid state.…”
Section: Introductionmentioning
confidence: 99%